Banque du Liban PLS Financing - Hamdoun, Diala (2020)
The objective of the research is to present a risk sharing Sharia-compliant financing scheme that reduces to a greater extent the exposure of Islamic Lebanese banks to displaced commercial risk (DCR) and encourages them to use modes of financing that are based on profit and loss sharing (PLS). In this context, a financial structure that is based on BDL circular 331 is proposed as a viable solution worth considering towards promoting PLS and mitigating DCR as well as competing on a level playing field with conventional banks. A model is developed to measure DCR under both risk sharing and BDL financing schemes and to assess the impact of introducing BDL financing on DCR mitigation. Using numerical simulations, the analysis shows that, for any particular investment, DCR can be reduced substantially by choosing BDL guarantee scheme as the mode of financing, thus paving the way for Lebanese Islamic banks to start providing PLS financing to their customers.